ANTI-INFLAMMATORY ACTIVITY OF METHANOL EXTRACT OF NIEBUHRIA APETALA (ROTH) DUNN – IN VITRO MODELS: Inflammatory property of Niebuhria apetala - RAJESH A; DOSS A; TRESINA PS; MOHAN VR (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: The objective of this study was to determine the anti-inflammatory activity of methanol extract of Niebuhria apetala and its possible mechanism of action. Methods: Methanol extract of Niebuhria apetala leaf (NAL) was assessed for its anti-inflammatory activity by in vitro methods. Using albumin denaturation assay, proteinase inhibitory activity, membrane stabilization, and antilipoxygenase activity at different concentrations, in vitro anti-inflammatory activity was estimated. The standard drug used for this purpose was aspirin. Results: Methanol extract NAL at a concentration range of 100–500 μg/ml significant (p<0.01) protects the heat-induced protein denaturation. At the concentration of 500 mg/ml, NAL showed significant (p<0.01) inhibition of protease inhibitory action. Heat-induced hemolysis of erythrocyte, hypotonicity-induced hemolysis, and lipooxygenase activity were significant (p<0.01) inhibited at the concentration of 500 μg/ml. Conclusion: Finally, the present study indicates that methanol extract of Niebuhria apetala can be a potential source of anti-inflammatory agent.